Acid-base catalysis II : proceedings of the International Symposium on Acid-base Catalysis II, Sapporo, December 2-4, 1993 - International Symposium on Acid-base Catalysis 1993 : Sapporo-shi, Japan); Hattori, Hideshi; Misono, M. (Makoto), 1939-; Ono, Yoshio, 1939-; ScienceDirect eBooks (Tokyo : Kodansha ; Amsterdam ; New York : Elsevier, 1994)
Solid acid catalysts are already being used in various processes in petroleum refining and are presently being studied intensively in both academic and applied fields for usage in a variety of reactions. Solid base catalysts are also gaining increasing recognition as potential catalysts. Both acidic and basic catalysts are promising not only with respect to acid and base-catalyzed reactions but also in materials sciences, such as the production of adsorbents, sensors, ceramics, etc. The present volume presents the text of 21 invited oral presentations and 58 poster presentations. The material covers a wide range of aspects on acid-base catalysis, from quantum chemistry to industrialized processes.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Catalysis -- Congresses; SCIENCE -- Chemistry -- Physical & Theoretical; Catalysis; Electronic books